AB0773 The Treatment with Denosumab plus Biologic Dmards in Patients with Rheumatic Chronic Diseases Showed Efficacy and Safety. A Case Series. (15th July 2016) - Hernández-Cruz, B.; Leόn Rubio, P.; Rubio, E.; Lisbona, M.; Fernández, M.; Valenzuela, M.J.; Decán, D.; Ojeda García, C.; Leόn, M.; Ruiz, A.; Povedano Gόmez, J.
Abstract : Background: The T2T strategy of treatment in severe inflammatory rheumatic diseases includes the use of biologic DMARDs (bDMARDs). However, the combination of two or more bDMARDs is not recommended due to toxicity, mainly infections. These patients had high risk of osteoporosis (OP) and its treatment is at least as important as the rheumatic disease. For this, the use of the combination of denosumab (DNS) plus bDMARD is increasing. Objectives: To know the prevalence of patients in treatment with DNS + bDMARD. To describe the inflammatory rheumatic disease and the OP. To know the frequency of severe adverse events of the combination. Methods: Design: An observational, retrospective, case series in common clinical practice. Methods: Nine rheumatologists were trained about design, protocol and data management. They reviewed all the clinical charts of patients with bDMARDs and identified those with at least one prescription of DNS. Of each case 53 variables were filled in a database, and the database was re-reviewed in order to verify the data. The statistical analysis was done with descriptive statistic. The incidence density rate for adverse events was calculated. Results: 1, 540 clinical charts were reviewed (569 of the HUVM and 971 of the HUVR), 38 cases of patients with DNS+bDMARD were found. The prevalence was 2.46%. They were female (36, 95%), with RA (28, 74%), SLE (2, 5%), and APs (2, 5%) and others. The mean (p25-p75) age at the rheumatic disease diagnostic was 49 (35–62) years old; the mean age at the OP diagnostic was 61 (54 - 68). The bDMARD were ETN (16, 42%), RTX (9, 24%), ADA (4, 10%), INF (3, 8%), ABA (3, 8%), TCZ (2, 5%) y GOLI (1, 3%) and the duration of the bDMARD treatment was of 60 (25–120) months. In addition, the most common synthetic DMARD used was MTX in 15 (40%) cases, and the dose was 15 mg/week (7.5 – 20). In 26 (67%) cases corticosteroids were used and the dose was 5 mg/day (5–10). Most of them had a mixed OP (glucocorticoid related and postmenopausal), n=26, 72% and in 5 cases the OP was postmenopausal. Fragility fractures (FF) previous to DNS were found in 9 cases (23%). The FF were peripheral (5, 13%); 2 (5%) vertebral FF and 2 (5%) with both of them. The patients received a mean of 3 (2–6) doses of DNS, with a duration of DNS treatment of 14.7 (6 – 37.9) months. The baseline FRAX score calculated without BMD for major osteoporotic FF was 13 (5.6 – 31) and for hip FF was 3.8 (0.7 – 16). The BMD showed T-score of femoral neck of -2.5 (-1.3 - -3.1) and total lumbar of -2.4 (-1 - -3.5). There were three cases of incident FF (5.07 FF x 100 patient/year). The adverse events were three urinary tract infections, and one of soft tissue. The infections were mild and treated with PO antibiotics. The rate was 6, 75x 100 patients/year. There were not severe infections, admissions to the emergency room, neither deaths. Conclusions: The frequency of the combination of DNS + bDMARD is low. This combination is used in patients with inflammatory rheumatic disease of a major length, damage and long treatment with steroids. The efficacy of DNS was the expected with no increased in toxicity. Disclosure of Interest: None declared